2006
DOI: 10.1038/nmat1631
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of dopamine-modified quantum dots and effects on biological systems

Abstract: Semiconductor quantum dots (QDs) have been widely used for fluorescent labelling. However, their ability to transfer electrons and holes to biomolecules leads to spectral changes and effects on living systems that have yet to be exploited. Here we report the first cell-based biosensor based on electron transfer between a small molecule (the neurotransmitter dopamine) and CdSe/ZnS QDs. QD-dopamine conjugates label living cells in a redox-sensitive pattern: under reducing conditions, fluorescence is only seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
256
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(273 citation statements)
references
References 28 publications
13
256
0
2
Order By: Relevance
“…Free radical generation by lipodots Clarke et al for QD560-dopamine in A9 cells, 28 and in our previous studies for non-targeted QD655 in Du145 cells. 31,36 Silver and Ou 40 postulated that fluorescence quenching could be attributed to the interaction of QDs with cellular molecules, particularly lysosomal enzymes.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Free radical generation by lipodots Clarke et al for QD560-dopamine in A9 cells, 28 and in our previous studies for non-targeted QD655 in Du145 cells. 31,36 Silver and Ou 40 postulated that fluorescence quenching could be attributed to the interaction of QDs with cellular molecules, particularly lysosomal enzymes.…”
supporting
confidence: 59%
“…21,22 Besides imaging, QDs are now emerging as therapeutic agents alone 23 or in combination with external radiation. [24][25][26] It has been recently shown that QDs irradiated with UV radiation, [27][28][29] blue light, photodynamic application. The most likely mechanism of photosensitized action of QDs is photogeneration of excitons and electron-hole pairs (e − and h + ) 32 and subsequent electron transfer to oxygen adsorbed on the QD surface forming a superoxide (O 2 − ) free radical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small biomolecules include quantum dots modified with dopamine via EDC chemistry (Clarke et al 2006(Clarke et al , 2008, with serotonin via a PEG spacer (Rosenthal et al 2002) or gold nanoparticles decorated with sugar molecules (de la .…”
Section: (Iii) Peptides Proteins Enzymes and Antibodiesmentioning
confidence: 99%
“…26,27 However, this ligand conjugation can produce some disadvantages such as a quenching of fluorescence, induction of toxicity, and distribution to other recognized organs. 27,28 We developed theranostic liposomes for brain delivery without the need for ligand association.…”
Section: 15mentioning
confidence: 99%